Evaluation of miRNA Profile and Its Relationship with Metabolic Disorders in Obese and Pre-Obese Patients - Kargun, Kursat; Aygen, Erhan; Ebiloglu, Mehmet Fatih; Alayunt, Naci Omer; Dalkilic, Luetfiye Kadioglu (Mdpi, 2025)
Obesity is a growing global public health concern, with its prevalence rapidly increasing in Turkey, leading to severe consequences. Genetic factors, particularly mutations in structural genes and microRNAs (miRNAs) involved in gene expression regulation have been widely investigated in obesity research. This study aimed to explore the role of obesity-associated miRNAs and their potential interaction with vascular response alterations. A total of 60 obese and pre-obese patients and 26 age- and sex-matched healthy controls from the General Surgery Department of F & imath;rat University Medicine School were included. The expression levels of 93 miRNAs were analyzed in 86 samples using the Fluidigm Biomark RT-PCR system, with 5S RNA as the housekeeping gene. Significant differences were observed in weight, BMI, cholesterol, triglyceride levels, and lymphocyte counts between the groups (p < 0.0001). Several miRNAs, including hsa-miR-148a-3p, hsa-miR-503-3p, hsa-miR-34a-5p, and hsa-miR-199a-3p, were significantly downregulated in obese patients. Additionally, gender-specific differences in miRNA expression were identified. These findings indicate that miRNAs play a crucial role in obesity pathophysiology and could serve as potential biomarkers and therapeutic targets for obesity treatment.
Keywords: fludeim; miRNA; pre-obese; obese